Fragmentation of the 4He2 dimer with the emission of three or four electrons by fast highly charged projectiles - Najjari, B.; Zhang, S. F.; Ma, X.; Voitkiv, A. B. (Frontiers in Physics, 2023)
We investigate the fragmentation of the helium dimer, ^4He_2, into He^2+ + He^+ and He^2+ + He^2+ ions in collisions with fast highly charged projectiles. We discuss the main physical mechanisms driving these processes. We explore the energy and angular distributions of the ionic fragments produced in collisions of the dimer with 1 GeV/u U^92+ and 11.37 MeV/u S^14 projectiles and also present the total fragmentation cross sections. According to our results, the fragmentation in these collisions is fully dominated by the direct removal of three or four electrons from the dimer by the projectile in a single collision. Our results also suggest that the total fragmentation cross sections depend on the the binding energy I_He_2 of the dimer, being roughly proportional to I_He_2 .